2008
DOI: 10.2737/rmrs-rn-33
|View full text |Cite
|
Sign up to set email alerts
|

New procedure for sampling infiltration to assess post-fire soil water repellency

Abstract: Abstract-The Mini-disk Infiltrometer has been adapted for use as a field test of post-fire infiltration and soil water repellency. Although the Water Drop Penetration Time (WDPT) test is the common field test for soil water repellency, the Mini-disk Infiltrometer (MDI) test takes less time, is less subjective, and provides a relative infiltration rate. For each test, the porous base plate of the MDI is placed on the soil surface and the amount of water that passes into the soil in one minute is measured.Thousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 6 publications
4
64
0
3
Order By: Relevance
“…Briggs et al (2012) observed extreme water repellency (water drop penetration test >2 h) for a freshly produced ponderosa pine (Pinus ponderosa) derived charcoal, but older carbon under forest floor layers was less water repellent. Unlike the hydrocarbons created during a fire, where extreme temperature gradients force hydrocarbons into the soil profile (Robichaud et al, 2008), biochar does not coat mineral soil particles but causes water repellency of the soil surface because it is a hydrophobic substance until it is sufficiently wetted. Biochar, coated particles, or charcoal from fire may alter water movement into the soil profile by preventing water infiltration into the mineral soil (DeBano, 2000).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Briggs et al (2012) observed extreme water repellency (water drop penetration test >2 h) for a freshly produced ponderosa pine (Pinus ponderosa) derived charcoal, but older carbon under forest floor layers was less water repellent. Unlike the hydrocarbons created during a fire, where extreme temperature gradients force hydrocarbons into the soil profile (Robichaud et al, 2008), biochar does not coat mineral soil particles but causes water repellency of the soil surface because it is a hydrophobic substance until it is sufficiently wetted. Biochar, coated particles, or charcoal from fire may alter water movement into the soil profile by preventing water infiltration into the mineral soil (DeBano, 2000).…”
mentioning
confidence: 99%
“…Estimating changes in soil hydrologic processes after biochar additions is important because water-repellent soils have an impact on infiltration rates (Doerr et al, 2000Robichaud et al, 2008. Past studies have shown increased water retention of biochar-amended agricultural soils (Novak et al, 2009), and some infiltration research has been conducted on naturally occurring black C (Briggs et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures used for these measurements were taken from Robichaud et al, 2008. The suction of the MDI was adjusted to 1cm, which is the suggested setting for post fire soil infiltration to provide capillarity suction and maintain a constant pressure while keeping the instrument from leaking (Decagon Devices, Inc., Pullman, WA).…”
Section: Infiltration (Mdi)mentioning
confidence: 99%
“…A water drop was applied to the soil surface at 1 and 3 cm depth and the residence time of the water drop to infiltrate was recorded. The classification to determine the degree of water repellency was taken from the USFS BAER procedures, and threshold class of WDPT: <10 s (weak), 10-40 s (moderate), and >40 s (strong) (Robichaud et al, 2008).…”
Section: Water Repellencymentioning
confidence: 99%